Analysis of phthalate plasticizer migration from PVDC packaging materials to food simulants using molecular dynamics simulations and artificial neural network. (1st July 2020) - Wang, Xiujuan; Song, Meng; Liu, Suting; Wu, Sizhu; Thu, Aung Myat
Highlights: An improved RBF ANN predicted the migration of phthalate plasticizer (MCC = 0.95). High temperature and n -hexane environments accelerated the migration of DEHP. Migration temperature had significant effect on the migration. Molecular dynamics simulations were conducted on three PVDC/DEHP/FS migration systems. Thermodynamic compatibility was analyzed by the two-component solubility parameters. Abstract: Based on the experimental data of gas chromatography-mass spectrometry, an improved artificial neural network was first established to predict the migration of 2-ethylhexyl phthalate (DEHP) plasticizer from poly(vinylidene chloride) (PVDC) into food simulants (ie., heptane, ethanol and water). The sensitivity analysis indicated that temperature acted as a crucial factor influencing the migration values of DEHP. Then, a combined experimental and molecular dynamic (MD) simulation was performed to understand the migration kinetics and the mechanism of DEHP. Hansen solubility parameters of three component ( δ d, δ p, δ h ) were simplified into two-component solubility parameters ( δ vdW, δ e ), and the tuple was successfully applied to describe the interactions between PVDC and food simulants. The MD results showed that high interaction energy and fractional free volume in PVDC/DEHP/food simulant systems accelerated the migration of DEHP. These fundamental studies would provide significant insights into the migration of environmental contaminants.